A third molar from Rathfarnham, Dublin, and the patterning cascade model. (9th August 2018) - Clark, Melissa A.; Guatelli‐Steinberg, Debbie
Abstract: The patterning cascade model (PCM) explains variation in cusp morphology in mammalian teeth. According to the PCM, cusp development is constrained by the time and space available for morphogenesis and by signalling molecules that create inhibitory zones around enamel knots, thereby preventing the formation of new enamel knots within a circumscribed region surrounding previously formed enamel knots. New enamel knots can only form outside of these inhibitory zones. A tooth with more cusps would therefore be expected to have smaller intercusp distances relative to crown size than a tooth with fewer cusps. This paper seeks to ascertain whether a young adult (68:1) excavated from a medieval site in Rathfarnam, County Dublin, Ireland. This unusual six‐cusped, five‐rooted left maxillary third molar was found during an assessment of skeletal remains at the National Museum of Ireland. This tooth deviates from the expected phenotype of between four and five cusps and two and three roots for third molars (M3s). To evaluate whether this tooth conforms to PCM predictions, bucco‐lingual and mesio‐distal diameters and intercusp distances were measured. The approximate crown area is 149.78 mm 2 . The ratio of intercusp distance to the approximate crown area (i.e., the relative average intercusp distance) is 0.351. This ratio is the lowest in the sample and falls well below the means of the relative average intercusp distance of all M3s (0.496) as well as all molars (0.486) in the sample. These results suggest that the unusual crown morphology of this tooth does not represent a deviation from the PCM. This upper left third molar exhibits partial root completion, whereas the remaining M3s of this individual exhibit complete root growth. We speculate that given the delayed developmental stage of this tooth, its unusual morphology might be related to a shift in developmental timing.